2022
DOI: 10.1177/14651165221140230
|View full text |Cite
|
Sign up to set email alerts
|

As the twig is bent, the tree is inclined? The role of parental versus own education for openness towards globalisation

Abstract: Citizens with higher levels of education are consistently found to be more open to immigration and European integration than those with less education. However, the literature has neglected the issue of whether educational divides in anti-globalisation sentiment result from people's own educational attainment or whether they are a consequence of deep-rooted positions of disadvantage across generations. In this article, we address the question to what extent the attitudes towards globalisation of intergeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Student leaders are trained to relate with each member, understand their peculiarities and foster cooperation with a view to achieving shared goals. By implication, people with higher levels of education are expected to be more open to globalisation due to exposure to liberal values in education (Kunst et al, 2023). Having good knowledge of the group members helps youth leaders to coordinate group activities, "assign certain members to tasks, and allocate resources in a way that promotes common goals" (Tackett et al, 2022;p.…”
Section: Whenever I Want To Make Decisions On Leadership Programme I ...mentioning
confidence: 99%
“…Student leaders are trained to relate with each member, understand their peculiarities and foster cooperation with a view to achieving shared goals. By implication, people with higher levels of education are expected to be more open to globalisation due to exposure to liberal values in education (Kunst et al, 2023). Having good knowledge of the group members helps youth leaders to coordinate group activities, "assign certain members to tasks, and allocate resources in a way that promotes common goals" (Tackett et al, 2022;p.…”
Section: Whenever I Want To Make Decisions On Leadership Programme I ...mentioning
confidence: 99%
“…The globalization-cleavage account depicted on the left-hand side of Figure 1 suggests that selfcategorized losers and winners of globalization primarily differ in their attitudes on issues associated with globalization, that is, international trade and market integration, European integration, and immigration. Relying on objective socio-economic markers to classify individuals as losers or winners of globalization, previous studies have shown that those with less formal education, as well as production workers, tend to be more globalization-sceptic across these different facets of globalization (e.g., Bovens & Wille, 2017;de Vries, 2018;de Wilde et al, 2019;Kriesi et al, 2008Kriesi et al, , 2012; on the causal nature of this education divide, also see: Kunst et al, 2020;Kunst, 2022). We add to this literature by studying how attitudes vary among self-categorized globalization losers and winners.…”
Section: Issue Attitudes Of Self-categorized Losers and Winners Of Gl...mentioning
confidence: 99%
“…Similarly, some studies have also pointed out the role of educational mobility on perception of social phenomena. For instance, educational attainment is seen as an important predictor for openness towards globalisation, but as Kunst et al (2023) show using European Social Survey data, there is an enduring influence of parental educational level on the respondents' views. Using the same data, Creighton et al (2022) found that upward educational mobility can moderate antipathy towards immigration.…”
Section: Literature Reviewmentioning
confidence: 99%